A Study on Temperature Sensing Bulb of Thermal Expansion Valve (Zhileng xuebao)
Charging characteristic of TEV temperature sensing bulb is one of the most affective factors of TEV performance.Refrigeration systems are often unstable because of bulb pressure fluctuations caused by oscillation of back air temperature of compressor.Temperature and pressure characteristics of TEV bulb with adsorption filler in R410a system was studied.It was found that adsorption filler increase the time constant of pressure change caused by bulb temperature rising and the dimension of adsorption filler de...